Analysis of Leading Sectors in Padang Pariaman District and West Sumatra Province Using Methods (DLQ, SLQ, and Shift Share) - Ramadhani, Febi; Voni, Salsa; Nikmah, Isnadiatun; Sari, Puspa; Labaika, Ratna; Hardianti, Khustiah; Mutia, Agustina (PT Inovasi Pratama Internasional, 2024)
The current complex regional development has encouraged intense competition between regions. To improve people's welfare, local governments need to increase the competitiveness of their regions. the measure of measuring regional economic growth is known as the Gross Regional Domestic Product (GDP). The purpose of the research conducted by the current author is to measure differences in the development of economic growth in the province of West Sumatra and the districts/cities of West Pasaman using the SLQ & DLQ analytical method, analysis shift shares. This study uses a quantitative descriptive approach. The data used are secondary data, namely research data obtained from the Central Statistics Agency (BPS) of West Sumatra Province and West Pasaman Regency/City in the form of Gross Regional Domestic Product (GRDP) data on the basis of constant prices (ADHK). ). The data used are 2018 & 2022, namely research by analyzing the data tested statistically and interpreting them in the form of descriptive sentences. Results from SLQ & DLQ analysts Based on the combined results of SLQ and DLQ analysis during the 2018 & 2022 observation period, the DLQ value> 1. This means that almost all economic sectors have the potential for faster development, and other economic sectors have a DLQ <1, which means that a commodity or sector with a score less than one is not a regional leading sector and still needs special attention for development.